Management of Stress in Culture Fish - Suguna, T. (International Journal of Bio-resource and Stress Management, 2021)
Over the last three decades, the commercial aquaculture has experienced spectacular growth. Many species have gone from small scale regional production to large scale global production. Concomitant with the rapid growth there also has been the increased occurrence of problems that accompany all agricultural endeavours. All the problems are stress influenced leading to diseases, impacting the profitability of the industries. In aquaculture also inspite of the unprecedented development of the intensified culture practices many economical problems have arise that are threatening the sustainability of culture systems. The root cause for all is stress. The word, “stress” is very common butreflects vast effective results. It is an invisible factor, influencing the survivality, growth, reproduction, production in culture fish especially. It is much easier for diseases to proliferate in the culture environment than in wild. Defining what levels of stressors are normal and acceptable is not easy. A level of stressor that is problematic under one set of environmental conditions might not be the same under another. The susceptibility of disease occurrence differs within species and age groups. Different stress factor such as inadequate physico chemical and microbial quality of culture water, poor nutritional stems and high stocking density can cause infection by opportunistic pathogens. In aquaculture, the stress plays major role on production, productivity, sustainability of the culture, economic loss and degradation of economic standards. A summation of causes for the acute and chronic stressors will enlighten the aqua farmers, scientists and fishery officials in designingenvironmentally friendly controlling measures, in obtaining higher yields.